The Principalâ€™s Leadership and Performance Result - Annisya, Annisya; Ramadan, Zaka Hadikusuma (Jurnal Ilmiah Sekolah Dasar, 2021)
Teacher performance was currently not optimal; this can be seen from the low learning outcomes of students. one of the factors that influence the success of teacher performance was the Principal's leadership. Therefore, research was conducted that aimed to analyze the Principal's leadership with the teacher's performance.Â  The type of research conducted was descriptive qualitative. The data was collected by interviewing head master, 3 school staff and selected students from 2 students. The data collection methods used are interviews, observations, and documentation. Analysis of the data used analysis techniques from Miles and Huberman. The results stated that good principal leadership in planning, organizing, deploying, coordinating, and supervising will affect teacher performance in performing designing tasks, carrying out learning, assessing learning, conducting guidance, and performing additional tasks. So, the Principal's leadership was good, then the teacher's performance was good, which directly affected the quality of learning. To improve teacher performance, the headmaster must conduct a supervised program to help teachers carried out their duties.